2014
DOI: 10.1120/jacmp.v15i6.4970
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of treatment plans using various treatment techniques for the radiotherapy of cutaneous Kaposi's sarcoma developed on the skin of feet

Abstract: The purpose of this study was to investigate the plan qualities of various treatment modalities for the radiotherapy of cutaneous Kaposi's sarcoma developed on the skin of the foot. A total of six virtual targets were generated on the skin of the foot in CT images. Five types of treatment plans were generated using photon beams (PB), electron beams (EB), high‐dose‐rate (HDR) brachytherapy with a Freiburg flap applicator, intensity‐modulated radiation therapy (IMRT), and volumetric‐modulated arc therapy (VMAT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…When comparing the technique described in this work with others, even state‐of‐the‐art radiotherapy techniques such as IMRT are not better appropriate for the treatment of skin cancer at an irregular surface of a patient, such as at the scalp, because a considerable amount of dose is given to the normal tissue beneath the skin with these techniques . Although Park et al demonstrated that VMAT was more effective in treating skin cancer at an irregular surface (skin cancer on foot) compared to HDR with surface applicator, electron beam therapy with multiple fields, or 3D conformal radiation therapy (3D‐CRT), also with VMAT, considerable doses were delivered to the normal tissue underneath the skin owing to the penetrating property of photons . Sung et al demonstrated that scattering foil free electron beam scanning therapy could reduce doses to the brain considerably for total scalp irradiation by MC simulation; however, considerable modification of the commercial linac was needed to apply this technique, which is nearly impossible to achieve in clinical settings .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When comparing the technique described in this work with others, even state‐of‐the‐art radiotherapy techniques such as IMRT are not better appropriate for the treatment of skin cancer at an irregular surface of a patient, such as at the scalp, because a considerable amount of dose is given to the normal tissue beneath the skin with these techniques . Although Park et al demonstrated that VMAT was more effective in treating skin cancer at an irregular surface (skin cancer on foot) compared to HDR with surface applicator, electron beam therapy with multiple fields, or 3D conformal radiation therapy (3D‐CRT), also with VMAT, considerable doses were delivered to the normal tissue underneath the skin owing to the penetrating property of photons . Sung et al demonstrated that scattering foil free electron beam scanning therapy could reduce doses to the brain considerably for total scalp irradiation by MC simulation; however, considerable modification of the commercial linac was needed to apply this technique, which is nearly impossible to achieve in clinical settings .…”
Section: Discussionmentioning
confidence: 97%
“…Some studies suggested the utilization of high‐dose rate (HDR) brachytherapy with a surface mold for total scalp irradiation . Although HDR utilizing a surface mold showed good local control for total scalp irradiation, this technique delivers considerable doses to OARs, since the Ir‐192 radioisotope of HDR emits gamma rays . In this respect, Wojcicka et al recommended that HDR with a surface mold should be used for less extensive lesions on the scalp, not for total scalp .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several studies have suggested HDR brachytherapy with a surface applicator, IMRT or VMAT as alternative to electron beam therapy to treat skin cancer on the scalp or extremities [3, 6, 2224]. The photon-electron combined technique was even developed to improve dose distribution on scalp [25].…”
Section: Discussionmentioning
confidence: 99%
“…Electron beam therapy is the best treatment option for shallow tumors located near flat surfaces of a patient’s body. However, if the patient surface is irregular, such as the scalp or foot, the penetrating power of an electron beam is modified in proportion to the off-axis distance, which results in heterogeneous delivery of the dose to a shallow target volume, such as those for skin cancer [ 3 , 5 , 6 ]. Therefore, modulated electron radiation therapy (MERT) has been suggested by several studies [ 7 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Volumetric modulated arc therapy (VMAT) modulating the treatment parameters which are gantry speed, multi-leaf collimator (MLC), and dose rate simultaneously is a novel technique in the field of radiation therapy [1][2][3]. For this reason, VMAT has been gradually used in the clinic and the prescription doses could be delivered to target volumes with sparing normal tissues with similar plan quality and monitor unit (MU) ef-JRPR fectiveness, compared to intensity modulated radiation therapy (IMRT) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%